2019
DOI: 10.1177/1745499919846013
|View full text |Cite
|
Sign up to set email alerts
|

Examining a model of scholarship for social justice

Abstract: The purpose of this study is to measure the impact of international scholarship programs for social justice – a case study of the Ford Foundation International Fellowships Program (IFP), the first model of scholarships for social justice. The human capability approach advanced by Amartya Sen is selected to conceptualize the measurement of the impacts. This study attempts to propose an alternative approach, which allows scholarship sponsors to see scholarship impact on the matter of people’s capabilities, rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This idea is embodied in the model of the Ford Foundation’s IFP program (see Dassin et al, 2014b; Musa-Oito, 2018) where grantees were selected from among marginalized populations in the 22 target countries (providing access on a micro-level) while also expecting that the grantees would return to create national social change (macro-level outcomes). While national social change is difficult to measure, there are several scholars who point to the attempt of IFP alumni to engage in this work (Campbell & Lavallee, 2019; Kusakabe, 2014; Waluyo et al, 2019). That being said, there are also recognized barriers for marginalized people to acquire positions of leadership and drive widescale social change in their countries—despite their overseas education—especially when fighting against the status quo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is embodied in the model of the Ford Foundation’s IFP program (see Dassin et al, 2014b; Musa-Oito, 2018) where grantees were selected from among marginalized populations in the 22 target countries (providing access on a micro-level) while also expecting that the grantees would return to create national social change (macro-level outcomes). While national social change is difficult to measure, there are several scholars who point to the attempt of IFP alumni to engage in this work (Campbell & Lavallee, 2019; Kusakabe, 2014; Waluyo et al, 2019). That being said, there are also recognized barriers for marginalized people to acquire positions of leadership and drive widescale social change in their countries—despite their overseas education—especially when fighting against the status quo .…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia, international scholarships were credited with encouraging women to become professors in the male-dominated Cambodian academy (Maxwell et al, 2015). In a recent quantitative study, Waluyo et al (2019) found that IFP scholarship alumni had skills to change paths and respond to challenges as they emerged, which was related to their work to influence social change in 22 countries.…”
Section: Social Change and Social Justice In The Home Countrymentioning
confidence: 99%
“…Research on scholarship programs defines social change as shifts in society (Campbell & Neff, 2020 ) that “reduce injustice and increase well-being in all forms” (Dassin et al, 2018 , p. 5), including at the economic, social, cultural, political, and environmental levels. International education creates various pathways for social change (Clift et al, 2013 ; Dassin et al, 2018 ; Waluyo et al, 2019 ). Some scholarships contribute toward social change by providing discriminated and underserved populations access to a high-quality international education (Clift et al, 2013 ).…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…In addition, exposure to diverse cultures and ways of living during their study period helps alumni of international universities to reconsider their own culture, values, and identity; they essentially develop “cosmopolitan competencies” (Gu & Schweisfurth, 2015 ). This fact is expressed in their cross-cultural sensitivity (Waluyo et al, 2019 ) and ability to view factors from multiple angles (Tung & Lazarova, 2006 ). Hence, they tend to experience a sense of obligation and growing desire to give back to their home country and society (Arhin-Sam, 2019 as cited in Campbell et al, 2021b ; Baxter, 2019 ).…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation